2005
DOI: 10.1200/jco.2005.14.373
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of the Novel Retinoid, Bexarotene, and Gemcitabine Plus Carboplatin in Advanced Non-Small-Cell Lung Cancer

Abstract: Bexarotene can be safely added to platinum-based chemotherapy provided that there is aggressive prophylaxis of hypertriglyceridemia. The median time to progression and overall survival are promising and warrant further evaluation of bexarotene in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…RXR agonists (rexinoids) activate the RXR/RXR homodimers [58]. One such drug, Targretin (Ligand Pharmaceuticals, San Diego, CA) is used in the treatment of cutaneous T-cell lymphoma [59] and shows promise in certain sub-population of lung cancer patients [60]. Rexinoids have the potential to be used in combinations with other nuclear receptor agonists [61][62][63].…”
Section: Nuclear Retinoic Acid Receptors and Synthetic Retinoidsmentioning
confidence: 99%
“…RXR agonists (rexinoids) activate the RXR/RXR homodimers [58]. One such drug, Targretin (Ligand Pharmaceuticals, San Diego, CA) is used in the treatment of cutaneous T-cell lymphoma [59] and shows promise in certain sub-population of lung cancer patients [60]. Rexinoids have the potential to be used in combinations with other nuclear receptor agonists [61][62][63].…”
Section: Nuclear Retinoic Acid Receptors and Synthetic Retinoidsmentioning
confidence: 99%
“…Bexarotene is currently the only rexinoid approved by the FDA, for treatment of cutaneous T-cell lymphoma. Notably, bexarotene, either alone or in combination with erlotinib and various chemotherapeutic agents, has been tested in a variety of clinical trials for lung cancer (4)(5)(6)(7)(8)(9). Although bexarotene failed to increase overall survival as a single agent, subsets of patients responded to the drug, with highgrade hypertriglyceridemia identified as a biomarker of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous phase I/II trials investigating the efficacy and tolerability of bexarotene, both as monotherapy and as part of combination therapy to treat NSCLC, have shown mixed results with regard to the effect of bexarotene on time to progression and overall survival [20][21][22] . In order to elucidate the role of bexarotene, two phase III studies examined the use of bexarotene in combination with cisplatin/vinorelbine and in combination with carboplatin/paclitaxel, both in chemotherapy-naïve patients with advanced NSCLC, and found that bexarotene had no effect on time to progression or overall survival.…”
Section: Discussionmentioning
confidence: 99%